BENTHIC FORAMINIFERA AS BIOINDICATOR OF CORAL REEF ENVIRONMENTAL CONDITION BASED ON FORAM Index IN NATUNA ISLANDS, PROVINCE OF RIAU ISLANDS - Kinanti Gitaputri; Hikmat Kasmara; Tatang S. Erawan; Suhartati M. (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
Foraminifera is one of single-celled protozoa, living in the water environment especially marine waters. This organism can be used as bioindicator of environmental conditions of coral reefs through a simple index called FORAM Index. The purpose of this research are to obtain FORAM Index values​, to know any species of benthic foraminifera bioindicator of coral reefs environmental conditions that have been found and to find out whether there is a relationship between FORAM Index to the condition of coral reefs based on coral coverage percentage. The research used survey method on sediment sampling and measurement of environment parameters by P20 LIPI team in April 2011. Several important steps in this research such as sediment samples preparation, sample observation, and sample identification. The results showed that there were 80 species and 31 genera benthic foraminifera bioindicator of coral reefs environmental conditions were found in the Natuna Islands. The condition of coral reefs in the Natuna Islands based on FORAM Index (FI) values ​​ranged from 2.6 to 5.94, and overall there was a positive relationship between FORAM Index and the condition of coral reefs based on coral coverage percentage i.e., the increase of FI was followed by the increase of coral coverage percentage. However, in the terms of correlation there were several different results, there was a strong correlation and a weak correlation. Keywords: foraminifera, FORAM index, coral reef.